2022
DOI: 10.1128/mbio.02888-21
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Targeting of Hepatitis B Virus Covalently Closed Circular DNA Generates Transcriptionally Active Episomal Variants

Abstract: Hepatitis B virus infection can develop into chronic infection, cirrhosis, and hepatocellular carcinoma. Treatment of chronic hepatitis B requires novel approaches to directly target the viral minichromosome, which is responsible for the persistence of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The dependence of viral persistence on functional cccDNA makes this HBV replication intermediate an ideal target for achieving a sterilising cure from HBV infection. cccDNA targeting using TALENs or CRISPR/Cas9-based therapies has shown promise [ 55 , 56 , 57 , 58 ]. These gene editors mediate sequence-specific deleterious mutations within the HBV DNA [ 22 ].…”
Section: Adenoviruses As Vectors Of Gene Therapy Against Hbvmentioning
confidence: 99%
“…The dependence of viral persistence on functional cccDNA makes this HBV replication intermediate an ideal target for achieving a sterilising cure from HBV infection. cccDNA targeting using TALENs or CRISPR/Cas9-based therapies has shown promise [ 55 , 56 , 57 , 58 ]. These gene editors mediate sequence-specific deleterious mutations within the HBV DNA [ 22 ].…”
Section: Adenoviruses As Vectors Of Gene Therapy Against Hbvmentioning
confidence: 99%
“…Therefore, gene therapy that targets cccDNA holds a potential therapeutic avenue to attain complete clinical curing of CHB infection ( Maepa et al., 2015 ; Bloom et al., 2018 ). Multiple studies have investigated the application of CRISPR/Cas9 for targeting and cleavage of many essential loci of HBV such as cccDNA, surface antigen, and X gene in cell cultures or animal models ( Seeger and Sohn, 2014a ; Kennedy et al., 2015 ; Ramanan et al., 2015a ; Zhen et al., 2015 ; Yan et al., 2021 ; Martinez et al., 2022 ). Seeger and Shon demonstrated the first use of the CRISPR/Cas9 strategy to disrupt the HBV cccDNA.…”
Section: Applications Of Crispr/cas Technology In Targeting Viral And...mentioning
confidence: 99%
“…The presence of the cccDNA and incorporation of the viral DNA into the host genome accelerates the progression of CHB and the development of hepatocellular carcinomas ( Martinez et al., 2022 ). The CRISPR/Cas9 system successfully abolishes cccDNA, yet the integrated HBV DNA particles remain potent pro-oncogenic mediators.…”
Section: Applications Of Crispr/cas Technology In Targeting Viral And...mentioning
confidence: 99%
“…Another recent study showed that the RNP delivery of CRISPR/Cas9 in HBV-infected HepG2-NTCP cells induced DSBs in cccDNA, which affected HBV replication. Moreover, Cas9-induced effects were sustained even after RNP degradation/loss of detection, suggesting stable changes due to transcriptional interference (Martinez et al, 2022). However, the efficacy of LNP-based CRISPR/Cas RNP delivery targeting the HBV genome remains to be investigated using a bona fide in vivo HBV infection model.…”
Section: Non-viral Vectors For Clustered Regularly Interspaced Short ...mentioning
confidence: 99%
“…With the advent of the CRISPR/Cas technology, several studies have reported varying degrees of inhibition of HBV replication and/or cccDNA formation using the CRISPR/Cas9 system with different delivery tools (Figure 2; Lin et al, 2014;Seeger and Sohn, 2014;Dong et al, 2015;Lin et al, 2015;Liu et al, 2015Liu et al, , 2018Ramanan et al, 2015;Wang et al, 2015;Zhen et al, 2015;Li H. et al, 2016;Seeger and Sohn, 2016;Zhu et al, 2016;Li et al, 2017Li et al, , 2018Kostyusheva et al, 2019;Kayesh et al, 2020;Suzuki et al, 2021;Yan et al, 2021;Martinez et al, 2022;Wang D. et al, 2022). Notably, it is difficult to efficiently quantify cccDNA (Wang Z. et al, 2022), and accurate quantification of intrahepatic cccDNA is important for assessing the efficiency of anti-HBV therapy.…”
Section: Introductionmentioning
confidence: 99%